Analisis Sensitivitas terhadap Keunggulan Komparatif dan Keunggulan Kompetitif Komoditas Tuna di Kabupaten Malang Jawa Timur - Yeni Sari Wulandari (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2021)
Malang Regency is one of the areas that has a big influence on capture fisheries in East Java, especially in producing tuna. According to BPS data in 2017, tuna is second in export value after shrimp. Therefore, Malang has a strategic value in the development of capture fisheries, especially in commodities of tuna, mackerel and skipjack. this opportunity, can improve the regional economy, make a potential advantage and make this commodity competitive in the international market. In addition, the development of capture fisheries business, especially tuna commodity in Malang, must also be supported by government intervention that sided with fishermen. Data was collected by means of observation, interviews, and literature study. Sources of data used are primary and secondary data. The sample used is 13 ship owners. Respondents in this study consisted of: 4 manols, 10 pengambek, 13 ship owners and 3 wholesalers, so that the total respondents obtained were 30 respondents. The analysis used is sensitivity analysis using DRCR and PCR values. Sensitivity is seen by the change in the rupiah exchange rate of 10%. The results showed that under normal conditions the value of DRCR was 0.21 and the value of PCR was 0.46. Meanwhile, the strengthening and weakening of the rupiah against US$ 10% resulted in the DRCR value of 0.21 to 0.24. at the time of strengthening with the initial condition value from 0.23 to 0.21. Thus, the tuna fish business still has a comparative advantage despite the strengthening and weakening of the rupiah against the US$. From the results of this study, strategies to maintain the competitiveness of tuna commodities at Malang regency with changing conditions can be done by 1) optimizing the use of inputs 2) facilitating skilled fishermen and 3) using environmentally friendly technology in accordance with recommendations from the Ministry of Fisheries and Marine Affairs. so that productivity increases so that it can meet the export quota.